2013
DOI: 10.1177/147470491301100506
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Relevance Facilitates Visual Information Processing

Abstract: Visual search of the environment is a fundamental human behavior that perceptual load affects powerfully. Previously investigated means for overcoming the inhibitions of high perceptual load, however, generalize poorly to real-world human behavior. We hypothesized that humans would process evolutionarily relevant stimuli more efficiently than evolutionarily novel stimuli, and evolutionary relevance would mitigate the repercussions of high perceptual load during visual search. Animacy is a significant component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
5
31
1
Order By: Relevance
“…The findings of the present study add to studies that have shown animate objects permeate visual attention in visual search, change blindness, and inattentional blindness tasks (Calvillo & Jackson, 2014;Jackson & Calvillo, 2013;New et al, 2007). These previous findings suggest that animate objects are prioritized in visual scenes.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The findings of the present study add to studies that have shown animate objects permeate visual attention in visual search, change blindness, and inattentional blindness tasks (Calvillo & Jackson, 2014;Jackson & Calvillo, 2013;New et al, 2007). These previous findings suggest that animate objects are prioritized in visual scenes.…”
Section: Discussionsupporting
confidence: 60%
“…Weimer, Gerdes, and Pauli (2013) found that participants have a greater skin conductance response to a spider than a flower in an inattentional blindness task, even when the spider was not reported. This physiological indicator of arousal may explain why animate objects are better detected in visual search tasks (Jackson & Calvillo, 2013) and better remembered in memory tasks (Nairne et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sha et al, 2015). Behavioural studies have shown that animate objects are more often consciously perceived in rapid serial visual presentations (RSVP) (Evans & Treisman, 2005;Guerrero & Calvillo, 2016;Hagen & Laeng, 2017), more quickly found in visual search (Jackson & Calvillo, 2013), elicit faster responses in discrimination tasks (Carlson, Ritchie, Kriegeskorte, Durvasula, & Ma, 2014;Ritchie, Tovar, & Carlson, 2015), and animate words are better retained in working memory (Nairne, VanArsdall, Pandeirada, Cogdill, & LeBreton, 2013). Aggregated, these findings point to a preferential visual processing of animate objects, most likely also reflected in the representational organisation of the visual stream (Carlson et al, 2014;Ritchie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Visual Search Efficiency is Greater for Human Faces Compared to Animal Faces Items in the environment that are of high biological significance appear to be located more efficiently than other items (e.g., Jackson, 2013; Öhman, 2007; Öhman, Flykt, & Esteves, 2001; Öhman, Soares, Juth, Lindström, & Esteves, 2012), though the proximate cause of this efficiency is debated (e.g., Horstmann & Bauland, 2006; Horstmann, Becker, Bergmann, & Burghaus, 2010; Horstmann, Lipp, & Becker, 2012; Yantis & Egeth, 1999). From an evolutionary perspective, according to the Animate Monitoring Hypothesis, human and nonhuman animals were the most important categories of visual stimuli for ancestral humans to monitor, as they presented challenges and opportunities for survival and reproduction, such as threats, mates, food, and predators (New, Cosmides, & Tooby, 2007; Orians & Heerwagen, 1992).…”
mentioning
confidence: 99%